Analysis of universal gas leak detector of hazardous gases using IOT. (2022) - Dinesh, D.; Nithin Mowshik, A.; Meyyappan, M.; Kowtham, M.
Abstract: There are numerous hazardous toxic gases, the majority of which are produced by sewers, landfills, mining plants, biogas plants, and other sources. Hazardous toxic gases include ammonia, hydrocarbons, hydrogen sulphide, and carbon monoxide, all of which are extremely dangerous and can cause headaches, lung cancer, dizziness, nausea, and other symptoms. There are also several advanced robots available to reduce the risk factor of working in hazardous situations, but they are not available at an affordable price. Some would like to recommend a cost-effective device that proactively ensures the lives of employees with the Long Range Module (LORA module), and it's known as an IOT-based universal gas detector and health monitoring device, which has three configurable devices, two of which are portable and one of which is wearable and contains an Message Queue (MQ) series sensor. A portable device detects toxic gases and alerts workers, allowing gases to settle. Heartbeat sensing devices detect a person's heartbeat. In case of any emergency, the LORA module sends an alert message to a supportive person and shares the location with a nearby ambulance and hospital.